2013
DOI: 10.1016/s0924-9338(13)76257-6
|View full text |Cite
|
Sign up to set email alerts
|

1167 – Prader-willi syndrome psychobehavioral profile in a clinic based sample

Abstract: BackgroundMaladaptive behaviors and cognitive impairment can be main problems in patients with Prader-Willi Syndrome. Understanding difficulties underlying the maladaptive behavior through early diagnosis and management allow tremendous improvement in the whole clinical picture.AimTo study the psychobehavioral deviations in a sample of Egyptian children with Prader-Willi syndrome and possible relation to genotype.MethodsWe included 15 out of 72 patients of both sexes, aged from 5–15 years old from the National… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Before the last review was written [Dykens et al, ], all publications investigating ASD symptoms in PWS had taken place in the United States or select Western European countries (United Kingdom, Netherlands, Belgium, and Italy). Since that review, publications have emerged from other countries, including Egypt [Ali et al, ] and Japan [Ogata et al, ; Song et al, ], confirming the presence of ASD symptomatology in more diverse samples of those with PWS.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Before the last review was written [Dykens et al, ], all publications investigating ASD symptoms in PWS had taken place in the United States or select Western European countries (United Kingdom, Netherlands, Belgium, and Italy). Since that review, publications have emerged from other countries, including Egypt [Ali et al, ] and Japan [Ogata et al, ; Song et al, ], confirming the presence of ASD symptomatology in more diverse samples of those with PWS.…”
Section: Discussionmentioning
confidence: 93%
“…Studies that reported ASD symptoms in individuals with PWS are summarized in Table . Notably, each of these except one [Ali et al, ] had a mean sample age of >10 years. Fewer than half of the studies included non‐PWS ASD comparison groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, there has been a growing recognition of the potential relationship between Prader-Willi Syndrome and Autism Spectrum Disorder (10). Through clinical observation, it is noticed that some of the behavioral features of Prader-Willi Syndrome overlap with those found in individuals with Autism Spectrum Disorder (8). Thus, we believe that our results from these screening methods are generalizable to the early screening of those with ALP in PWS patients while also providing a better reflection of crosssectional functional levels and other associated deficits which may pose significant impact to their education, career, and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Prader-Willi Syndrome (PWS) is a type of syndromic ASD and rare genetic disorder that can be caused by one of the three genetic abnormalities: a paternal deletion of the 15q11.2-q13 region, maternal uniparental disomy (mUPD), or an imprinting defect (ID) (6,7). Studies suggest that the prevalence of ASD in PWS ranges from 12.7 to 40% with significant overlaps in their clinical features (8)(9)(10)(11)(12)(13)(14). The early identification and screening of individuals with PWS that are at risk for ASD will help facilitate early intervention, which can significantly impact their prognosis, thus highlighting the need for further studies.…”
Section: Introductionmentioning
confidence: 99%